2018
DOI: 10.1002/slct.201802046
|View full text |Cite
|
Sign up to set email alerts
|

2‐Hydroxyethyl‐Substituted Pd‐PEPPSI Complexes: Synthesis, Characterization and the Catalytic Activity in the Suzuki‐Miyaura Reaction for Aryl Chlorides in Aqueous Media

Abstract: In recent years, PEPPSI (Pyridine‐Enhanced Precatalyst Preparation Stabilization and Initiation) complexes have attracted attention in organometallic chemistry. This study contains the synthesis of the 2‐hydroxyethyl‐substituted Pd‐PEPPSI complexes and their catalytic activity in the Suzuki‐Miyaura reaction aryl chlorides in aqueous media. The Pd‐PEPPSI complexes have been prepared from the 2‐ hydroxyethyl‐substituted N‐heterocyclic carbene (NHC) precursors, palladium chloride and 3‐chloropyridine. The Pd‐PEPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
(43 reference statements)
0
14
0
4
Order By: Relevance
“…The FT‐IR data clearly indicated the presence of ν (OH) at 3431, 3475, 3458, 3347, 3408, 3438, 3397, 3469, 3465 and 3230 cm −1 for the (NHC)PdI 2 (pyridine) complexes ( 1 a‐j ), respectively. These NMR and FT‐IR data are consistent with literature ,. The results of the elemental analysis were evaluated and it was observed that the calculated values were very close to the found values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The FT‐IR data clearly indicated the presence of ν (OH) at 3431, 3475, 3458, 3347, 3408, 3438, 3397, 3469, 3465 and 3230 cm −1 for the (NHC)PdI 2 (pyridine) complexes ( 1 a‐j ), respectively. These NMR and FT‐IR data are consistent with literature ,. The results of the elemental analysis were evaluated and it was observed that the calculated values were very close to the found values.…”
Section: Resultsmentioning
confidence: 99%
“…(C−Br). However, the electron‐donor group on the benzene ring strengthens the bond by reducing the polarity of the covalent bond between the bromide atom and the carbon atom in the para position (C−Br) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This synthesis approach has revolutionized the production of advanced materials [15,16,17,18], pharmaceuticals [19,20,21], agrochemicals [21,22], liquid crystals [23], and natural or biologically active compounds [24,25,26,27,28], etc. Numerous attractive strategies have been developed to address the ample scope of this catalytic process including the utilization of palladium nanoparticles [29,30,31,32,33,34,35], or palladium immobilized on magnetic nanoparticles [36] and natural supports [37], use of nucleophilic carbene ligands (mostly NHCs) [38,39,40,41,42,43,44,45,46], Schiff bases [47,48], water-soluble ligands like poly(ethylene glycol)-functionalized N-heterocyclic carbenes [49], thiourea [50] or phosphines [51,52], induction by microwave (MW) acceleration [53,54], use of “greener” solvents, such as water [55,56,57,58,59,60,61,62,63,64,65] (activated by MW [66,67] or in catalysis under micellar conditions [68] for enhancing the solubility of the aromatic halide), water–DMF […”
Section: Introductionmentioning
confidence: 99%